2008
DOI: 10.1056/nejmoa0706790
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and the Risk of End-Stage Renal Disease

Abstract: Although the absolute risk of ESRD in women who have had preeclampsia is low, preeclampsia is a marker for an increased risk of subsequent ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
276
2
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(301 citation statements)
references
References 35 publications
12
276
2
11
Order By: Relevance
“…[97][98][99][100] Recently, the American Heart Association has recognized preeclampsia as a novel risk factor for CVD in women. 101 It is currently thought that the background metabolic milieu of women (ie, shared risk factors) confer risk for both preeclampsia and for long-term CVD.…”
Section: Long-term Complications Of Preeclampsiamentioning
confidence: 99%
“…[97][98][99][100] Recently, the American Heart Association has recognized preeclampsia as a novel risk factor for CVD in women. 101 It is currently thought that the background metabolic milieu of women (ie, shared risk factors) confer risk for both preeclampsia and for long-term CVD.…”
Section: Long-term Complications Of Preeclampsiamentioning
confidence: 99%
“…44 In addition, we have no reliable data available on total number of PE pregnancy to study the effect of repetitive PE on eGFR while other studies already showed a dose-response curve on cardiovascular and renal prognosis. 3,35 Other limitations are the slight differences in pregnancy to follow-up interval between the fHP and fPE groups, the absence of urinary albumin measurement, and the absence of data on social economic status, which is correlated with a lower eGFR. 45 In a subgroup of the PREVFEM cohort, it was suggested that the fPE might have a higher social economic status because they were reported to have a higher education, 46 but in the full cohort, we could not find any differences in modifiable indicators of socioeconomic status affecting the eGFR (BMI and metabolic profile).…”
Section: -24mentioning
confidence: 99%
“…1,2 In addition, they are reported to have a 5-to 12-fold increased risk to develop end-stage kidney disease (ESKD) in studies with follow-up times ranging from 6 to 17 years postpartum. [3][4][5] The risk of chronic kidney disease (CKD) is estimated to be increased 4 to 10 times. 4 The exact course of renal function after preeclampsia that precedes the development of CKD and ESKD remains unclear and hinders the development of strategies to earlier identify the women at highest risk.…”
mentioning
confidence: 99%
“…However, long-term renal and cardiovascular risks have been associated with a history of maternal placental syndromes such as PE, suggesting that PE is more than an isolated disease of pregnancy (3). Increased risk of developing future chronic hypertension and CVD has been observed in women diagnosed with PE during pregnancy compared with normotensive women (4)(5)(6). While the American Heart Association guidelines in 2011 recognized PE as cardiovascular risk factor (7), it is unknown whether the increased risk can be attributed to factors that develop during pregnancy or to prepregnancy predisposing factors that Preeclampsia (PE), associates with long-term increased risk for cardiovascular disease in women, suggesting that PE is not an isolated disease of pregnancy.…”
Section: Introductionmentioning
confidence: 99%